Anticomunism, the Early American Conservative Movement and the Liberal Consensus (1955-1964) - David Sarias Rodríguez (Culture & History Digital Journal, 2022)
This article re-examines the role that anticommunism played during the emergence of the early American conservative movement. Through a detailed re-assessment of published and archival material it challenges the two main assumptions consistently reproduced by the literature, and according to which evangelical anticommunist played a doubly crucial role. According to the established view, anticommunism set apart conservative intellectuals and activists from their liberal counterparts and, secondly, acted as the element holding together different ideological strands within the conservative community. These pages demonstrate that anticommunism itself was, in fact, never as dividing an issue as both conservatives and liberal activists claimed. Instead, relatively marginal differences of opinion about the Cold War were blown out of all proportion and employed by both conservatives and progressives as a tool in the midst of intensely sectarian partisan struggles. Similarly, anticommunism was never an element of consensus within a wider conservative community that at this point included traditionalist intellectuals, libertarians and adherents to the populist radical right. In fact, anticommunism often acted as an element furthering already existing ideological tensions.